Rasva- ja valkuaisainepitoisuuden suhteesta suomalaisessa maidossa - Hietaranta, Matti; Niemelä, Kaleva (Agricultural and Food Science, 1954)
The present investigation deals with the determination of the relation between the fat and protein contents of Finnish milk as well as the possibility of estimating the casein content by the formol titration method described by Walker, modified by McDowall and Dolby. The ratio of protein to fat in Finnish milk is lower than in the other Northern Countries. In the past 30 years the ratio of protein to fat in Finnish milk has been slightly reduced, apparently owing both to the feeding and to the influence of breeding, which have tended to increase the fat content. It is well known that in milk samples with a high fat content the protein content is proportionally lower than in milk with a fat content below the average. The correlation between the fat and total protein contents both in bulk milk and in milk samples from various herds is, from a practical point of view, the same as the correlation between their fat and casein contents. The smaller the portion of milk involved, the more difficult it is to estimate its protein content from the fat percentage. The correlation between fat and protein contents in bulk milk is, again, much more stable than in milk from individual cows. The correlation coefficient for the fat and protein contents in bulk milk is + 0.726 ± 0.06, the corresponding coefficient in milk from various herds is + 0.535 ± 0.05 and in milk samples from individual cows, + 0.432 ± 0.07. The respective correlation coefficients for the fat and casein contents are: + 0.735 ± 0.05; + 0.590± 0.03 and + 0.277 ± 0.09. The casein percentages in milk samples from various herds and in those from individual cows have been determined by the formol titration method. For the calculation of the conversion factor between formol valne and true casein content, the latter has also been determined by the A.O.A.C. method, after which the conversion factor has been given as the ratio between the A.O.A.C. value and the formol valne. The accuracy of the various determinations with formol titration is indicated by the standard deviations (table 2). The standard deviations of the conversion factors indicate that the casein content of milk samples from various herds can be estimated with an accuracy of ± 5 %. The accuracy of casein estimations in milk samples from individual cows is on the average ± 13 %, which cannot be considered adequate even for practical purposes. In addition, the conversion factors reveal seasonal fluctuations which are due to the proportional variations between casein and other protein components in various milk samples.